Dendritic Cells and T Cells Interact Within Murine Afferent Lymphatic Capillaries - Hunter, Morgan Campbell; Teijeira, Alvaro; Montecchi, Riccardo; Russo, Erica; Runge, Peter; Kiefer, Friedemann; Halin, Cornelia (Frontiers in Immunology, 2019)
Afferent lymphatic vessels contribute to immunity by transporting antigen and leukocytes to draining lymph nodes (LNs) and are emerging as new players in the regulation of peripheral tolerance. Performing intravital microscopy in inflamed murine ear skin we found that migrating dendritic cells (DCs) and antigen-experienced effector T cells spend considerable time arresting or clustering within afferent lymphatic capillaries. We also observed that intralymphatic T cells frequently interacted with DCs. When imaging polyclonal T cells during an ongoing contact-hypersensitivity response, most intralymphatic DC-T cell interactions were short-lived. Conversely, during a delayed-type-hypersensitivity response, cognate antigen-bearing DCs engaged in long-lived MHCII-(I-A/I-E)-dependent interactions with antigen-specific T cells. Long-lived intralymphatic DC-T cell interactions reduced the speed of DC crawling but did not delay overall DC migration to draining LNs. While further consequences of these intralymphatic interactions still need to be explored, our findings suggest that lymphatic capillaries represent a unique compartment in which adaptive immune interaction and modulation occur.